3D mapping of the neutral X-ray absorption in the local interstellar medium: the Gaia and XMM-Newton synergy - Gatuzz, Efrain; Rezaei, S. Kh; Kallman, Timothy R.; Kreikenbohm, Annika; Oertel, Mirjam; Wilms, Jörn; Garcia, Javier (Monthly Notices of the Royal Astronomical Society, 2018)
We present a three-dimensional map of the hydrogen density distribution in the Galactic interstellar medium. The hydrogen-equivalent column densities were obtained from the Exploring the X-ray Transient and variable Sky project (EXTRAS) which provides equivalent NH values from X-ray spectral fits of observations within the XMM-Newton Data Release. EXTRAS include multiple fits for each source, allowing an accurate determination of the equivalent column densities, which depends on the continuum modelling of the spectra. A cross-correlation between the EXTRAS catalogue and the first Gaia Data Release was performed in order to obtain accurate parallax and distance measurements. We use a Bayesian method explained in Rezaei Kh. et al. (2017) in order to predict the most probable distribution of the density at any arbitrary point, even for lines of sight along which there are no initial observation. The resulting map shows small-scale density structures which could not have been modelled by using analytic density profiles. In this paper, we present a proof of concept of the kind of science possible with the synergy of these catalogues. However, given the systematic uncertainties connected to the source identification and to the dependence of NH on the spectral model, the present maps should be considered qualitatively at this point.
Keywords: ISM: atoms; ISM: structure; Galaxy: structure; X-rays: ISM

SIXTE: a generic X-ray instrument simulation toolkit - Dauser, Thomas; Falkner, Sebastian; Lorenz, Maximilian; Kirsch, Christian; Peille, Philippe; Cucchetti, Edoardo; Schmid, Christian; Brand, Thorsten; Oertel, Mirjam; Smith, Randall; Wilms, Jörn (Astronomy & Astrophysics, 2019)
We give an overview of the SImulation of X-ray TElescopes (SIXTE) software package, a generic, mission-independent Monte Carlo simulation toolkit for X-ray astronomical instrumentation. The package is based on a modular approach for the source definition, the description of the optics, and the detector type such that new missions can be easily implemented. The targets to be simulated are stored in a flexible input format called SIMPUT. Based on this source definition, a sample of photons is produced and then propagated through the optics. In order to model the detection process, the software toolkit contains modules for various detector types, ranging from proportional counter and Si-based detectors, to more complex descriptions like transition edge sensor (TES) devices. The implementation of characteristic detector effects and a detailed modeling of the read-out process allow for representative simulations and therefore enable the analysis of characteristic features, such as for example pile-up, and their impact on observations. We present an overview of the implementation of SIXTE from the input source, the imaging, and the detection process, highlighting the modular approach taken by the SIXTE software package. In order to demonstrate the capabilities of the simulation software, we present a selection of representative applications, including the all-sky survey of eROSITA and a study of pile-up effects comparing the currently operating XMM-Newton with the planned Athena-WFI instrument. A simulation of a galaxy cluster with the AthenaX-IFU shows the capability of SIXTE to predict the expected performance of an observation for a complex source with a spatially varying spectrum and our current knowledge of the future instrument.
CRIS-Team WoS Importer:2019-10-11

The EXTraS project: Exploring the X-ray transient and variable sky - De Luca, A.; Salvaterra, R.; Belfiore, A.; Carpano, S.; D'Agostino, D.; Haberl, F.; Israel, G. L.; Law-Green, D.; Lisini, G.; Marelli, M.; Novara, G.; Read, A. M.; et al. (Astronomy & Astrophysics, 2021)
Temporal variability in flux and spectral shape is ubiquitous in the X-ray sky and carries crucial information about the nature and emission physics of the sources. The EPIC instrument on board the XMM-Newton observatory is the most powerful tool for studying variability even in faint sources. Each day, it collects a large amount of information about hundreds of new serendipitous sources, but the resulting huge (and growing) dataset is largely unexplored in the time domain. The project called Exploring the X-ray transient and variable sky (EXTraS) systematically extracted all temporal domain information in the XMM-Newton archive. This included a search and characterisation of variability, both periodic and aperiodic, in hundreds of thousands of sources spanning more than eight orders of magnitude in timescale and six orders of magnitude in flux, and a search for fast transients that were missed by standard image analysis. All results, products, and software tools have been released to the community in a public archive. A science gateway has also been implemented to allow users to run the EXTraS analysis remotely on recent XMM datasets. We give details on the new algorithms that were designed and implemented to perform all steps of EPIC data analysis, including data preparation, source and background modelling, generation of time series and power spectra, and search for and characterisation of different types of variabilities. We describe our results and products and give information about their basic statistical properties and advice on their usage. We also describe available online resources. The EXTraS database of results and its ancillary products is a rich resource for any kind of investigation in almost all fields of astrophysics. Algorithms and lessons learnt from our project are also a very useful reference for any current and future experiment in the time domain.
CRIS-Team Scopus Importer:2021-07-16
Keywords: Astronomical databases: miscellaneous; Catalogs; Methods: data analysis; X-rays: general